THE CORRELATION BETWEEN STUDENTS' ISLAMIC MORAL VALUES AND THEIR ENGLISH ACHIEVEMENT IN THE IMPLEMENTATION OF THE SCIENTIFIC APPROACH THROUGH ICT OF CURRICULUM 2013 AT JUNIOR IDGH SCHOOLS IN KAMPAR REGENCY OF RIAU PROVINCE - Abdullah Hasan (AL-FIKRA, 2014)
The   main   goal    of   this    study   is  to  find     out   the correlation between  students'   Islamic  moral values    and   their English  achievement    in   the   implementation   of   the   Scientific Approach  Through ICT  of     Curriculum 2013     at  Junior  High Schools.  The   research utilizes  a  mixed  method  of  quantitative and   qualitative  research  with    a  quasi  experimental  study   of pretest-postest   non  equivalent control group design.  The  sample of  the   study   comprised  160   students   and   three   Junior  High schools  in  Kampar  regency  of  Riau   province.  The   schools  are State    Junior  High   School  number   1   (SMPN 1)  Bangkinang, Private Islamic Junior High   School of  Assalam  (M.Ts As-Salam) and      State    Junior  High   School  number   1  (SMPN 1) Kampar Timur.  The   scientific approach  with   three  aspects  of  attitude, skill     and     krwwledge    competencies    through       information Technology (ICT)and Islamic moral values  are  integrated in  this study.  Data   are  coUected using  a  test   to  measure  the  students' English  achievement;  then,    observation  and   questionnaire  are administered  to investigate  the  students'   Islamic moral values. Three  research  questions  are  proposed   in  this   research   The findings  show significant relationship between  English language achievement   and   Islamic  moral  values   through  the   scientific approach  through ICT  of  curriculum 2013.  At  last,   the  research finding  hopefully  able   to  become  a  model for  English  teaching instruction in Riau province locallly and  in Indonesia nationally.